Novel KCNJ16 variants identified in a Chinese patient with hypokalemic metabolic acidosis - Jianxiong Chen; Youqing Fu; Yan Sun; Xinlong Zhou; Qingming Wang; Cong Li; Haiming Yuan (Molecular Genetics & Genomic Medicine, 2023)
Abstract Background Biallelic pathogenic variants in the KCNJ16 gene result in hypokalemic tubulopathy and deafness (HKTD) (MIM #619406), which is a rare autosomal recessive disease characterized by hypokalemic tubulopathy with renal salt wasting, disturbed acid–base homeostasis, and sensorineural deafness. Currently, nine individuals with HKTD have been reported, and seven pathogenic variants in KCNJ16 have been revealed. Methods A 5‐year‐6‐month‐old Chinese female patient displayed hypokalemic metabolic acidosis, salt wasting, renin‐angiotensin‐aldosterone system (RAAS) activation, arrhythmia, myocardial damage, cardiogenic shock and secondary diffuse brain oedema. Trio‐based whole‐exome sequencing (WES) was applied to detect the genetic cause. Results Novel compound heterozygous variants, c.190A>C (p.Thr64Pro) and c.628C>G (p.His210Asp), in KCNJ16 were detected in the patient, and these variants were inherited from the patient's mother and father, respectively. Then, we systematically reviewed the available clinical manifestations of individuals with HKTD. We found that HKTD patients are at risk of cardiogenic shock and secondary diffuse brain oedema, which urges clinicians to make early diagnoses with prompt treatments. Conclusion These findings expand the variant spectrum of KCNJ16, enrich the clinical characteristics of HKTD, and provide a solid base for the genetic counseling, diagnosis and treatment of this condition.